Eventide : a novel - Haruf, Kent (Vintage Books, 2005)
A novel of small-town life in the high plains region around Holt, Colorado, follows the challenges, emotional upheaval, tragedies, and intertwined destinies of the local inhabitants as they cope with the changes they encounter.